Determinants of Tuberculosis Treatment Outcome among Patients Belonging to the Tea Tribe Community in Dibrugarh District of Assam - Bhupendra Narayan Mahanta; Tulika Goswami Mahanta; Nabanita Nirmolia; Swarnali Devi Baruah (Healthline)
Introduction: Certain social determinants like poverty, malnutrition, indoor air pollution, male gender, diabetes, and cancer are some identified risk factors of TB. The tea garden population as it is socio- economically backward are more vulnerable to get infected. Objective: To estimate the determinants of tuberculosis treatment outcomes among patients belonging to the tea tribe community in Dibrugarh District of Assam and to assess the quality of life using WHO-QoL (BREF) instrument. Method: A Community-based cross-sectional study was conducted in Dibrugarh District of Assam. A sample size of 930was calculated using nMaster2.0 software, CMC, Vellore, India. From the list of registered TB cases whose treatment was assigned hailing from tea estates,a required sample was selected using a computerized random number. Predesigned, pretested questionnaire was used to assess the demographic, socio-economic, environmental and health- seeking behaviour of the participants. Univariate and bivariate analysis was done. Results: Total participation was 785. Regarding environmental determinants, ventilation was very poor and 98.5% used firewood as fuel for cooking. The risk of passive smoking was present in 7.6% of households. Respondents who had a history of family members with chronic cough were present in 5.9%. Loss to follow up rate was 2.9% (23/786). Lack of energy and fatigue was experienced by 83.6%. Marital status, occupation, monthly income, type of family and ventilation were associated with treatment outcome. Gender and socio-economic status of the respondents were associated with knowledge attitude and practice on Hepatitis B among participants which was found to be statistically significant (p-value < 0.0001). Conclusion: Certain social and environmental determinants like monthly income, type of family, and inadequate ventilation influence the treatment outcome in the tea garden population. Knowledge and practice pattern for tuberculosis needs to be improved to prevent transmission and alteration in quality of life.